PP98 Occupational Therapy For Adult Persons With Cognitive Impairments: A Systematic Overview On Clinical Efficacy. (23rd December 2022) - Schnell-Inderst, Petra; Conrads-Frank, Annette; Stojkov, Igor; Krenn, Cornelia; Kofler, Lisa-Maria; Siebert, Uwe
Abstract : Introduction: Damage to the central nervous system (CNS) in adulthood, may lead to cognitive impairments. In Germany, occupational therapy is most often prescribed for neurological diagnoses, including stroke and traumatic brain injury (351 and 343 cases per 100, 000, respectively in 2018). For cognitive impairments, the primarily prescribed remedies are sensorimotor-perceptive, motor-functional and neuropsychologically oriented treatment or training of cognitive performance. Here we report the results of a health technology assessment (HTA) report on the clinical efficacy of occupational therapy for patients with cognitive impairments. Methods: To assess clinical efficacy, a systematic overview was conducted based on published systematic reviews and HTA reports from the last ten years summarizing randomized controlled trials (RCTs) retrieved from four bibliographic databases. The target population included adult patients with cognitive impairments caused by diseases of the CNS, excluding moderate to severe dementia. The intervention studied is occupational therapy compared to no occupational therapy. Outcomes were cognitive abilities, independence, self-determination, health-related quality of life (QoL), and participation in activities of daily living (ADL). Results: Five systematic reviews comprising 1, 316 patients were included. There is evidence for a small statistically significant positive effect on "general cognitive function" (10 RCTs, n=470) and on ADL (4 RCTs, n= 405). A non-quantified positive effect was reported on behavior control (1 RCT, n=96), and conflicting evidence on QoL (2 RCTs, n=214). No effect was found for individual components of cognition (5 RCTs, n=202), self-efficacy (1 RCT, n=98) and social participation (2 RCTs, n=194). The level of the evidence was low for all endpoints due to the high risk of bias and small sample sizes. Conclusions: Based on this systematic overview, it cannot be demonstrated but also not ruled out that occupational therapy for cognitive impairment is an effective therapy for adults with cognitive impairments. The evidence is very uncertain due to small effects and high risk of bias, low statistical power, and heterogeneity of interventions and study populations.